The Governance Effect of the Media's News Dissemination Role: Evidence from Insider Trading - DAI, LILI; PARWADA, JERRY T.; ZHANG, BOHUI (Journal of Accounting Research, 2015)
ABSTRACT We investigate whether the media plays a role in corporate governance by disseminating news. Using a comprehensive data set of corporate and insider news coverage for the 2001–2012 period, we show that the media reduces insiders’ future trading profits by disseminating news on prior insiders’ trades available from regulatory filings. We find support for three economic mechanisms underlying the disciplining effect of news dissemination: the reduction of information asymmetry, concerns regarding litigation risk, and the impact on insiders’ personal wealth and reputation. Our findings provide new insights into the real effect of news dissemination.